Multiple copy number variation in a patient with Kleefstra syndrome - Thomas Nohama Lee; Henrique El Laden Rechetello; João Batista De Arêa Lima Júnior; João Pedro Fagoti Ferraz Cornelio; Naiara Bozza Pegoraro; Salmo Raskin; Liya Regina Mikami (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To report a rare case of a patient with a molecular diagnosis of Kleefstra syndrome (KS) who has four other chromosomal alterations involving pathogenic variants. Case description: Male patient, two years old, with global delay, including in neuropsychomotor development, ocular hypertelorism, broad forehead, brachycephaly, hypotonia, ligament laxity, unilateral single palmar crease and arachnoid cyst. The microarray-based comparative genomic hybridization (a-CGH) identified copy number variations (CNVs) in five regions: 9q34.3, 6p22.1, Yq11.223, Yp11.23, and 2q24.1. The heterozygous microdeletion in 9q34.3 involving the EHMT1 gene confirms the diagnosis of KS. Comments: The presence of pathogenic CNVs and/or those of uncertain significance, located on chromosomes 2, 6 and Y, may be contributing to a variability in the patient's clinical condition (arachnoid cyst, single palmar fold and ligament laxity), compared to other individuals with only KS genetic alteration, making the dignosis of the disease harder.